ANALISIS PENGARUH INFRASTRUKTUR PUBLIK TERHADAP PRODUK DOMESTIK BRUTO PERKAPITA DI INDONESIA - David Kaluge, Eko Fajar Cahyono, (Fakultas Ekonomi, UIN Maliki Malang, 2011)
This study aims to measure how far the influence of public infrastructure such as roads, electricity,Â and telephoneÂ to Gross Domestic Product in Indonesia. This research is based on the theory of classical and neoclassical economic growth which assumes that the infrastructure is physical capital that relate either directly or indirectly to economic growth. This research used error correction modelÂ analysis and time series data. Based on estimates found that public infrastructure have a significant and positive impact on Gross Domestic Product.